Answer: D. [tex]g(x) = (x-b)^2[/tex]
Explanation:
If we want to shift the curve some distance b to the right, then we'll need to replace x with x-b. What this effectively does is shift the xy axis itself b units to the left while the curve is fixed in place. This gives the illusion of the curve moving b units to the right.
Put another way: the old input x is updated to the new input x-b which is smaller by b units. This helps explain why the xy axis is shifted to the left this amount.
So that's how we go from [tex]f(x) = x^2[/tex] to [tex]g(x) = (x-b)^2[/tex]. You can think of it as [tex]g(x) = f(x-b) = (x-b)^2[/tex]